Sternal Fracture Fixation with a Steel Wire: The New “Timala” Technique - Rabindra Bhakta Timala; Nirmal Panthee (Journal of Trauma and Injury)
Purpose Traumatic sternal fractures are rare but quite disabling injuries. Timely fixation of sternal fractures reduces pain and prevents respiratory complications. However, the fixation technique should be simple, effective, and readily available in local circumstances. Methods From January 2014 to March 2020, seven patients with sternal fracture/ dislocation underwent steel wire fixation with the new “Timala” technique. In this technique, adjacent ribs are anchored with two steel wires to form an “X” in front of the fractured segment of the sternum. Patients were followed up clinically and radiologically. Results Six of the patients were men and one was a female. Five of them had injuries due to falls and two were injured in road traffic accidents. Their age ranged from 18 years to 76 years, with a median age of 41 years. All seven patients experienced immediate recovery from pain and showed evidence of fracture healing on postoperative chest X-rays and clinical examinations. Conclusions Anchoring ribs to fix the sternum with steel wire is a safe, effective, easily available, and reproducible method to fix sternal fractures or dislocations.